Female Entrepreneurial Intentions in Pakistan: A Theory of Planned Behavior Perspective - Sarwar, Ambreen; Ahsan, Qurratulain; Rafiq, Nazia (Frontiers in Psychology, 2021)
With theoretical underpinnings in the theory of planned behavior, this research aims at investigating how women’s entrepreneurial intentions might develop in Pakistan. The survey of 216 female students revealed that psychological capital plays an important role in shaping women’s entrepreneurial commitment which in turn results in increased intentions to opt for entrepreneurship as career. Additionally, it was observed that social support moderates the indirect relation in such a way that in the presence of high social support, the association between psychological capital and intentions via commitment is further strengthened. Because women face comparatively more barriers in paid career, therefore it was necessary to study the mechanism and driver that can improve their entrepreneurial intentions, since they represent an untapped resource that might be utilized to further the economic prospects of a country. The study bridges a significant knowledge gap in utilizing psychological capital to enhance female’s entrepreneurial intentions, who are under constant pressure of juggling multiple roles at work and home.